TWO-STAGE DECISION-MAKING IN ONLINE FASHION MSMES: AN ISLAMIC MANAGERIAL ECONOMICS PERSPECTIVE IN PEKALONGAN, INDONESIA - Dwi Yoga Prasetyo; Kresna Mustika; Tamamudin; Ali Muhtarom (Academic Bright Collaboration, 2026)
This study aims to explore and map the strategic decision-making sequences of online fashion MSMEs in Pekalongan through the lens of Islamic managerial economics. It specifically investigates how Islamic ethical constraints, such as the avoidance of gharar (uncertainty) and the pursuit of Siddiq (honesty), reconfigure the cognitive process of choosing between digital platforms and marketing techniques. Following an interpretivist paradigm, this research employed a qualitative multiple-case study design using three distinct cases: a traditional batik artisan, a work trousers manufacturer, and a contemporary jeans retailer. Data were collected through semi-structured interviews using a